Implications of Shariah on the voluntary disclosure of Indonesian listed companies - Annuar, Hairul Azlan (Emerald Group Publishing Limited, 2014)
Purpose – The purpose of this paper is to investigate and compare the extent of voluntary disclosure in the annual reports of Shariah- and non–Shariah-compliant companies in Indonesia. Further, the study examines the relationship between voluntary disclosure and company characteristics (i.e. size of company, profitability, type of auditor, type of industry and ownership structure). Design/methodology/approach – Voluntary disclosure was measured using a disclosure index with 30 items and content analysis of the 2009 annual report. Statistical analysis included descriptive, Mann–Whitney U and regression. Findings – The result revealed that there is a statistically significant difference in the quantity and quality of voluntary disclosure value of Shariah- and non–Shariah-compliant companies. For regression results, the company size significantly influences the quantity of voluntary disclosure while the quality of voluntary disclosure is affected by company size and type of industry. Research limitations/implications – Although this study only analyses voluntary disclosure in the annual report for a single year (2009), it is hoped to provide a description of the voluntary disclosure in Shariah- and non–Shariah-compliant companies. Practical implications – The findings might be used by regulators to set regulations that encourage the quantity and quality of disclosure practice of Shariah-compliant companies to expand the scope of disclosure related to religious activities. Originality/value – This study measures voluntary disclosure using the disclosure index based on Indonesian regulations and the quantity and quality measurement of Shariah-compliant companies, which may differ from previous Indonesian studies.